2014
DOI: 10.1208/s12248-014-9605-8
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits the AKT/NF-κB Signaling via CpG Demethylation of the Promoter and Restoration of NEP in the N2a Cell Line

Abstract: Abstract. Curcumin (CUR), a non-toxic polyphenol from Curcuma longa, has been investigated as a potential therapy with anti-inflammatory and anti-oxidative effects for Alzheimer's disease (AD), which depicts features of chronic inflammatory environment resulting in cellular death. However, it remains largely unknown whether the anti-inflammatory effect of CUR in AD is associated with its property of CpG demethylation, which is another function of CUR with the most research interest during recent years. Neprily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 45 publications
(55 reference statements)
1
25
0
Order By: Relevance
“…Deng and colleagues (2014) [85] using bisulfite-sequencing PCR (BSP) assay, they demonstrated that the CpG sites in NEP gene were hypermethylated both in wild-type mouse neuroblastoma N2a cells (N2a/wt) and N2a cells stably expressing human Swedish mutant amyloid precursor protein (N2a/APPswe) associated with familial early onset AD. CUR treatment induced restoration of NEP gene via CpG demethylation.…”
Section: Research On Curcumin and Cell Models Of Alzheimer’s Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Deng and colleagues (2014) [85] using bisulfite-sequencing PCR (BSP) assay, they demonstrated that the CpG sites in NEP gene were hypermethylated both in wild-type mouse neuroblastoma N2a cells (N2a/wt) and N2a cells stably expressing human Swedish mutant amyloid precursor protein (N2a/APPswe) associated with familial early onset AD. CUR treatment induced restoration of NEP gene via CpG demethylation.…”
Section: Research On Curcumin and Cell Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…This CUR-mediated upregulation of NEP expression was also concomitant with the inhibition of AKT, subsequent suppression of nuclear transcription factor-κβ (NF-κβ) and its downstream pro-inflammatory targets including COX-2, iNOS in N2a/APPswe cells. This study represents the first evidence on a link between CpG demethylation effect on NEP and anti-inflammation ability of CUR that may provide a novel mechanistic insight into the anti-inflammatory actions of CUR as well as new basis for using CUR as a therapeutic intervention for AD [85]. …”
Section: Research On Curcumin and Cell Models Of Alzheimer’s Diseasementioning
confidence: 99%
“…One study showed that curcumin treatment induced the reactivation of the NEP gene via CpG demethylation. In curcumin-treated N2a/APPswe cells, the upregulation of NEP expression was also concomitant with AKT inhibition and the subsequent suppression of NF-κB and its downstream proinflammatory targets, including COX-2 and iNOS [38], Furthermore, the Fanconi anemia (FA) complementation group F (FANCF) gene plays an important role in the FA pathway and is frequently inactivated due to promoter hypermethylation in specific types of cancer [39]. Curcumin treatment produces a 5-fold increase in FANCF gene expression due to the demethylation of 12 of the 15 CpGs present in the promoter region [40].…”
Section: Introductionmentioning
confidence: 99%
“…(Melzig and Janka, 2003; Ayoub and Melzig, 2006; Kiss et al, 2006; Deng et al, 2014; Fujiwara et al, 2014). Green tea catechins were shown to be preventive in AD animal models via up-regulation of NEP (Lim et al, 2013).…”
Section: Pharmacological and Epigenetic Regulation Of Ade Genesmentioning
confidence: 99%